Immunometabolic signatures predict recovery from thyrotoxic myopathy in patients with Graves' disease. Issue 1 (30th December 2021) - Setoyama, Daiki; Lee, Ho Yeop; Moon, Ji Sun; Tian, Jingwen; Kang, Yea Eun; Lee, Ju Hee; Shong, Minho; Kang, Dongchon; Yi, Hyon‐Seung
Abstract: Background: Thyroid hormone excess induces protein energy wasting, which in turn promotes muscle weakness and bone loss in patients with Graves' disease. Although most studies have confirmed a relationship between thyrotoxicosis and muscle dysfunction, few have measured changes in plasma metabolites and immune cells during the development and recovery from thyrotoxic myopathy. The aim of this study was to identify specific plasma metabolites and T‐cell subsets that predict thyrotoxic myopathy recovery in patients with Graves' disease. Methods: One hundred patients (mean age, 40.0 ± 14.2 years; 67.0% female), with newly diagnosed or relapsed Graves' disease were enrolled at the start of methimazole treatment. Handgrip strength and Five Times Sit to Stand Test performance time were measured at Weeks 0, 12, and 24. In an additional 35 patients (mean age, 38.9 ± 13.5 years; 65.7% female), plasma metabolites and immunophenotypes of peripheral blood were evaluated at Weeks 0 and 12, and the results of a short physical performance battery assessment were recorded at the same time. Results: In both patient groups, methimazole‐induced euthyroidism was associated with improved handgrip strength and lower limb muscle function at 12 weeks. Elevated plasma metabolites including acylcarnitines were restored to normal levels at Week 12 regardless of gender, body mass index, or age ( P trend <0.01). Senescent CD8 + CD28 − CD57 + T‐cell levels in peripheral blood were positively correlated with acylcarnitine levels ( P  < 0.05) and decreased during thyrotoxicosis recovery ( P  < 0.05). High levels of senescent CD8 + T cells at Week 0 were significantly associated with small increases in handgrip strength after 12 weeks of methimazole treatment ( P  < 0.05), but not statistically associated with Five Times Sit to Stand Test performance. Conclusions: Restoring euthyroidism in Graves' disease patients was associated with improved skeletal muscle function and performance, while thyroid hormone‐associated changes in plasma acylcarnitines levels correlated with muscle dysfunction recovery. T‐cell senescence‐related systemic inflammation correlated with plasma acylcarnitine levels and was also associated with small increases in handgrip strength.